Re-positioning: Internationally educated teachers in Manitoba school communities - Block, Lee Anne (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
Internationally educated teachers (IETs) can change how cultural differences are perceived in school communities. Rather than mirroring dominant social norms, IETs can be an alternative to stereotypes and extend all students’ understanding of difference. This qualitative study examined how teacher agency is expressed by IETs in the context of a bridging program and in schools where IETs are employed as teachers in Manitoba. Their role in the school system is approached through considering agency as an effect. The analysis suggests that IETs act as cultural mediators and have the potential to become agents of change, if they find teaching positions within which they choose to position themselves as critical cultural mediators. Keywords: internationally educated teachers, position, teacher agency, cultural differences, immigrant